Calcium Lactate Pentahydrate Crystallization in the Presence of Pentanoic Acid - KIRAN YILDIRIM, BERÇEM; SAYAN, PERVİZ; SARGUT, SİBEL (WILEY-V C H VERLAG GMBH, 2018)
Calcium lactate crystallization was investigated in the presence of pentanoic acid in a mixed-suspension mixed-product removal (MSMPR)-type crystallizer. Filtration rate measurements were carried out to define the effect of pentanoic acid on the filtration characteristics of calcium lactate pentahydrate crystals. The average particle size, length-to-width ratio, and morphologies of calcium lactate pentahydrate crystals were also determined and examined as a function of pentanoic acid concentrations. The zeta potential of calcium lactate pentahydrate crystals was measured. Thermogravimetric and differential thermal analysis (TGA-DTA) as well as X-ray diffraction (XRD) were performed and Coats and Redfern's method was used to verify the kinetic parameters in the dehydration steps observed in the TGA curves.
Keywords: Calcium lactate pentahydrate; Crystallization; Fatty acid; Pentanoic acid; CHEESE; CRYSTAL